Acrylate copolymer adhesive, pressure-sensitive adhesive and preparation method thereof
By regulating the composition of the acrylate copolymer raw glue, a high molecular weight and narrow distribution acrylate copolymer is synthesized, which solves the problem of warping and deformation of existing pressure-sensitive adhesives under high temperature and high humidity conditions, and realizes a high-stability and low residual glue pressure-sensitive adhesive, which is suitable for the bonding of polarizers.
Patent Information
- Application Number
- CN202211721086.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-12-30
AI Technical Summary
Existing pressure-sensitive adhesives are prone to warping and deforming under high temperature and high humidity conditions, and it is difficult to take into account both the fit, light leakage resistance and low residual glue properties.
Acrylate copolymer raw glue is used to regulate the ratio of soft monomers, hard monomers, crosslinked monomers, initiators and solvents to synthesize high molecular weight and narrow distribution acrylate copolymers to form a pressure-sensitive glue that is resistant to ring measurement, has high stability and low residual glue.
The stability and fit of pressure-sensitive adhesives under high temperature and high humidity conditions are achieved, the residual adhesive volume is reduced, and the rework effect of polarizers is improved.
Smart Images

Figure BDA0004029750800000011 
Figure BDA0004029750800000031 
Figure BDA0004029750800000071
Abstract
Description
Technical Field
[0001] The invention relates to the field of pressure-sensitive adhesives, and in particular to an acrylic ester copolymer adhesive, a pressure-sensitive adhesive and a preparation method thereof. Background Art
[0002] In the display field, polarizer has always been an important device in liquid crystal display. Its main function is to control the polarization direction of light, so that the liquid crystal display device can display a specific image under different electrical signals. The polarizer is mainly composed of TAC on both sides and PVA in the middle. In order to make the polarizer better used in the display, it is necessary to apply a layer of pressure-sensitive adhesive on the polarizer to ensure that it is integrated with other display devices. Since the polarizer is very easy to warp and deform under high temperature and high humidity conditions, and at the same time, it is necessary to ensure that the high-cost polarizer can have a good repair effect, this requires the pressure-sensitive adhesive used for the polarizer to be resistant to warping and light leakage under high temperature and high humidity, and also needs to have good adhesion and low residual adhesive.
[0003] The performance of the pressure-sensitive adhesive is determined by the base adhesive. Therefore, it is necessary to provide a base adhesive that is resistant to warping and light leakage, has good adhesion and low residual adhesive properties to solve the above problems. Summary of the invention
[0004] In order to overcome the shortcomings of the prior art, the first object of the present invention is to provide an acrylic ester copolymer rubber, comprising the following raw materials in parts by weight:
[0005]
[0006] The weight average molecular weight of the acrylic ester copolymer raw rubber is 100-200W, and the PDI is 1-10.
[0007] Preferably, the soft monomer is butyl acrylate.
[0008] Preferably, the hard monomer is at least one of methyl acrylate, methyl methacrylate and isobornyl acrylate.
[0009] Preferably, the cross-linking monomer is at least one of hydroxyethyl acrylate, hydroxybutyl acrylate, acrylamide and acrylic acid.
[0010] Preferably, the initiator is at least one of a peroxide or an azo initiator.
[0011] Preferably, the solvent is ethyl acetate and / or toluene.
[0012] The second object of the present invention is to provide an acrylate copolymer pressure-sensitive adhesive, comprising the acrylate copolymer base rubber as described above; 100 parts of the acrylate copolymer base rubber further comprises: 0.01-0.5 parts of a cross-linking agent, 0.001-0.1 parts of a coupling agent, and 0.01-0.5 parts of an antistatic agent.
[0013] The third object of the present invention is to provide a method for preparing an acrylate copolymer pressure-sensitive adhesive, comprising the following steps:
[0014] 100 parts of acrylate copolymer, 0.01-0.5 parts of cross-linking agent, 0.001-0.1 parts of coupling agent and 0.01-0.5 parts of antistatic agent are mixed and stirred evenly in a certain proportion, coated on a release film, and dried to obtain a finished product.
[0015] Preferably, the release film has a thickness of 10-50 μm.
[0016] Preferably, the thickness of the adhesive film formed after coating on the release film is 5-30 μm.
[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention provides an acrylate copolymer rubber, comprising the following raw materials in parts by weight: 40-95 parts by weight of soft monomer; 5-40 parts by weight of hard monomer; 0.1-5 parts by weight of cross-linking monomer; 0.02-0.5 parts by weight of initiator; 50-200 parts by weight of solvent; the weight average molecular weight of the acrylate copolymer rubber is 100-200W, and the PDI is 1-10. The present invention also relates to its pressure-sensitive adhesive and preparation method. By regulating the molecular weight, molecular weight distribution and cross-linking system, the balance between ring resistance, viscosity and low residual adhesive is coordinated, thereby obtaining a pressure-sensitive adhesive for polarizers with ring resistance, high stability and low residual adhesive.
[0018] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention. The specific implementation of the present invention is given in detail by the following embodiments. DETAILED DESCRIPTION
[0019] The present invention is further described below in conjunction with specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.
[0020] The main problems with the prior art are: if the pressure-sensitive adhesive needs to have good adhesion, the gel rate of the pressure-sensitive adhesive needs to be reduced, but this will cause the peeling force to rise too high, resulting in residual adhesive when the pressure-sensitive adhesive is peeled off. Otherwise, the adhesion will deteriorate. The performance of the polarizer needs to be adjusted by adding additives in different proportions. The increase in small molecular weight additives will increase the instability of the pressure-sensitive adhesive under high temperature and high humidity. If you want to take all aspects of performance into consideration, the acrylate polymer needs to have the characteristics of high molecular weight, narrow distribution, and low residual monomers, which is challenging for the design of the synthesis process. In order to overcome the shortcomings of the existing pressure-sensitive adhesive, the present invention relates to an acrylate copolymer original glue, comprising the following raw materials in parts by weight:
[0021]
[0022] The weight average molecular weight of the acrylic copolymer raw rubber is 100-200W, and the PDI is 1-10. The present invention synthesizes high molecular weight, narrow distribution and low residual monomer acrylic copolymer by selecting monomers and controlling the synthesis process, thereby ensuring the balance of pressure-sensitive adhesiveness, lamination and reworkability.
[0023] In some embodiments, the soft monomer is butyl acrylate; butyl acrylate has a relatively high main modulus, a lower initial viscosity than isooctyl acrylate, is resistant to creep, and has a better die-cutting effect.
[0024] In some embodiments, the hard monomer is at least one of methyl acrylate, methyl methacrylate, isobornyl acrylate, acryloylmorpholine, tetrahydrofuran methacrylate, cyclohexyl acrylate, N-vinyl pyrrolidone, N,N-dimethylacetoacetamide, and tetrahydrofuran acrylate; the modulus is adjusted by using the hard monomer as an auxiliary.
[0025] In some embodiments, in order to obtain a better low-temperature aging effect, the cross-linking monomer is at least one of hydroxyethyl acrylate, hydroxybutyl acrylate, acrylamide, and acrylic acid.
[0026] In some embodiments, the initiator is at least one of a peroxide or an azo.
[0027] In some embodiments, the solvent is ethyl acetate and / or toluene. The synthesis process of the acrylate copolymer raw rubber is specifically as follows: the monomers are mixed and dissolved in the solvent ethyl acetate or toluene, heated to 50-80°C, one or more of the initiators peroxides or azos are added, reacted for 8-20 hours, and diluted to a solid content of 15-30% to obtain an acrylate copolymer. The present invention also relates to an acrylate copolymer pressure-sensitive adhesive, comprising the above acrylate copolymer raw rubber; 100 parts of the acrylate copolymer raw rubber also include: 0.01-0.5 parts of a cross-linking agent, 0.001-0.1 parts of a coupling agent, and 0.01-0.5 parts of an antistatic agent. The present invention regulates the polarizer pressure-sensitive adhesive based on the raw rubber, and the obtained product has better stability. The main advantages are the synthesis of high molecular weight and narrow distribution glue.
[0028] The present invention also relates to a method for preparing an acrylate copolymer pressure-sensitive adhesive, comprising the following steps:
[0029] 100 parts of acrylate copolymer, 0.01-0.5 parts of crosslinking agent, 0.001-0.1 parts of coupling agent, and 0.01-0.5 parts of antistatic agent are mixed and stirred evenly in a certain proportion, applied to the release film, and dried to obtain a finished product. Specifically, each component is mixed and stirred evenly in a certain proportion, applied to a release film of a certain thickness, forming a film of a certain thickness, and dried in an oven at 80-120°C for 2-5 minutes, and the aging condition is 35°C / 5 days.
[0030] It should be understood that the key points of the present invention are the proportion of carboxyl groups in the acrylate polymer and the molecular weight and molecular weight distribution of the original glue. The climbing effect of the pressure-sensitive adhesive after long-term standing can be adjusted by fine-tuning the proportion of carboxyl groups in the acrylate polymer. The main molecular weight and molecular weight distribution are controlled by controlling the solvent addition time and rate during the reaction process. Under the same gel rate, the higher the acrylic acid content, the more obvious the climbing is, and the easier it is to leave residual glue under the same standing time. At the same time, the smaller the molecular weight, the greater the peeling force, and the easier it is to leave residual glue. The weight-average molecular weight of the original glue must be guaranteed to be 100-200W, PDI is less than 9, 25°C storage modulus> 80KPa, 60°C storage modulus> 30KPa, so as to ensure the overall stability of the pressure-sensitive adhesive under high temperature and humidity.
[0031] In some embodiments, the release film has a thickness of 10-50 μm, preferably 38 μm. The release film of 38 μm has good stiffness and a shrinkage ratio that matches that of the polarizer.
[0032] In some embodiments, the thickness of the adhesive film formed after coating on the release film is 5-30 μm, preferably, the thickness is 25 μm.
[0033] Embodiment 1
[0034] 300g solvent ethyl acetate, 156g soft monomer butyl acrylate, 36g hard monomer benzyl acrylate, 6g cross-linking monomer hydroxyethyl acrylate, and 2g cross-linking monomer acrylic acid were put into a 1L four-necked flask, heated to 78°C, and 0.16g BPO was added to react for 10h, during which solvent dilution was required. After the reaction was completed, the temperature was lowered and diluted to 20% solid content to obtain acrylate copolymer 1. 100 parts of acrylate copolymer 1, 0.2 parts of toluene diisocyanate, 0.02 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, and 0.2 parts of antistatic agent were mixed and mechanically stirred for 10-15min. The stirred mixture was coated on a 50μm thick release film, baked in an oven at 120°C for 3min, attached to a polarizer, and aged at 35°C for 5 days to obtain sample 1.
[0035] Embodiment 2
[0036] 300 grams of solvent ethyl acetate, 156g of soft monomer butyl acrylate, 36g of benzyl acrylate, 4g of cross-linking monomer hydroxyethyl acrylate, and 4g of cross-linking monomer acrylic acid were put into a 1L four-necked flask, heated to 78°C, and 0.16g of BPO was added to react for 10 hours. During this period, solvent dilution was required. After the reaction was completed, the temperature was lowered and diluted to 20% solid content to obtain acrylate copolymer II. 100 parts of acrylate copolymer II, 0.2 parts of toluene diisocyanate, 0.02 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, and 0.2 parts of antistatic agent were mixed and mechanically stirred for 10-15 minutes. The stirred mixture was coated on a 50μm thick release film, baked in an oven at 120°C for 3 minutes, and attached to the polarizer to obtain sample II.
[0037] Comparative Example 1
[0038] 300 grams of solvent ethyl acetate, 156g of soft monomer butyl acrylate, 36g of benzyl acrylate, 6g of cross-linking monomer hydroxyethyl acrylate, and 2g of cross-linking monomer acrylic acid were put into a 1L four-necked flask, heated to 78°C, and 0.25g of BPO was added to react for 10 hours. During this period, solvent dilution was required. After the reaction was completed, the temperature was lowered and diluted to 20% solid content to obtain acrylate copolymer three. 100 parts of acrylate copolymer three, 0.2 parts of toluene diisocyanate, 0.02 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, and 0.2 parts of antistatic agent were mixed and mechanically stirred for 10-15 minutes. The stirred mixture was coated on a 50μm thick release film, baked in an oven at 120°C for 3 minutes, and attached to the polarizer to obtain sample three.
[0039] Comparative Example 2
[0040] 300g solvent ethyl acetate, 156g soft monomer butyl acrylate, 36g benzyl acrylate, 4g cross-linking monomer hydroxyethyl acrylate, and 4g cross-linking monomer acrylic acid were put into a 1L four-necked flask, heated to 78°C, and 0.25g BPO was added to react for 10h. During this period, solvent dilution was required. After the reaction was completed, the temperature was lowered and diluted to 20% solid content to obtain acrylate copolymer 4. 100 parts of acrylate copolymer 4, 0.2 parts of toluene diisocyanate, 0.02 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, and 0.1 parts of antistatic agent were mixed and mechanically stirred for 10-15min. The evenly stirred mixture was coated on a 50μm thick release film, baked in an oven at 120°C for 3min, and attached to a polarizer to obtain sample 4.
[0041] Comparative Example 3
[0042] 300 grams of solvent ethyl acetate, 156g of isooctyl acrylate, 36g of benzyl acrylate, 6g of cross-linking monomer hydroxyethyl acrylate, and 2g of cross-linking monomer acrylic acid were put into a 1L four-necked flask, heated to 78°C, and 0.16g of BPO was added to react for 10 hours. During this period, solvent dilution was required. After the reaction was completed, the temperature was lowered and diluted to 20% solid content to obtain acrylate copolymer V. 100 parts of acrylate copolymer V, 0.2 parts of toluene diisocyanate, 0.02 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, and 0.2 parts of antistatic agent were mixed and mechanically stirred for 10-15 minutes. The stirred mixture was coated on a 50μm thick release film, baked in an oven at 120°C for 3 minutes, attached to a polarizer, and aged at 35°C for 5 days to obtain sample V.
[0043] Comparative Example 4
[0044] 300g solvent ethyl acetate, 158g soft monomer butyl acrylate, 36g benzyl acrylate, and 6g cross-linking monomer hydroxyethyl acrylate were put into a 1L four-necked flask, heated to 78°C, and 0.16g BPO was added to react for 10h. During this period, solvent dilution was required. After the reaction was completed, the temperature was lowered and diluted to 20% solid content to obtain acrylate copolymer VII. 100 parts of acrylate copolymer VI, 0.2 parts of toluene diisocyanate, 0.02 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, and 0.2 parts of antistatic agent were mixed and mechanically stirred for 10-15min. The evenly stirred mixture was coated on a 50μm thick release film, baked in an oven at 120°C for 3min, attached to a polarizer, and aged at 35°C for 5 days to obtain sample VI.
[0045] Comparative Example 5
[0046] 300g solvent ethyl acetate, 160g soft monomer butyl acrylate, 36g benzyl acrylate, and 4g cross-linking monomer acrylic acid were put into a 1L four-necked flask, heated to 78°C, and 0.16g BPO was added to react for 10h. During this period, solvent dilution was required. After the reaction was completed, the temperature was lowered and diluted to 20% solid content to obtain acrylate copolymer VIII. 100 parts of acrylate copolymer VII, 0.2 parts of toluene diisocyanate, 0.02 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, and 0.2 parts of antistatic agent were mixed and mechanically stirred for 10-15min. The evenly stirred mixture was coated on a 50μm thick release film, baked in an oven at 120°C for 3min, attached to a polarizer, and aged at 35°C for 5 days to obtain sample VIII.
[0047] Comparative Example 6
[0048] 300g solvent ethyl acetate, 160g soft monomer butyl acrylate, 36g benzyl acrylate, and 4g cross-linking monomer acrylic acid were put into a 1L four-necked flask, heated to 78°C, and 0.16g BPO was added to react for 10h. During this period, solvent dilution was required. After the reaction was completed, the temperature was lowered and diluted to 20% solid content to obtain acrylate copolymer VIII. 100 parts of acrylate copolymer VIII, 0.2 parts of toluene diisocyanate, 0.02 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, and 0.2 parts of antistatic agent were mixed and mechanically stirred for 10-15min. The stirred mixture was coated on a 50μm thick release film, baked in an oven at 120°C for 3min, attached to a polarizer, and aged at 35°C for 5 days to obtain sample VIII.
[0049] The molecular weight and molecular weight distribution of acrylate copolymers 1-8 are shown in Table 1;
[0050] Table 1 Molecular weight and molecular weight distribution of different examples
[0051]
[0052] Performance tests were performed on Examples 1-2 and Comparative Examples 1-6 of the present invention, and the results are shown in Table 2:
[0053] Peel force test: Peel force is tested according to ASTM D 3330;
[0054] The heavy-duty test is to leave it at room temperature for 20 days and observe the surface of the back sticker by peeling off the polarizer;
[0055] 65℃ / 95% environmental test is tested in an aging test chamber;
[0056] The 80°C environmental test was conducted in an oven;
[0057] The thermal shock test is carried out in a thermal shock test chamber.
[0058] Table 2 Detection performance of different embodiments
[0059]
[0060] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation methods. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown here.
Claims
1. A method for preparing an acrylate copolymer pressure-sensitive adhesive, characterized in that: The following steps are involved: 300 g of solvent ethyl acetate, 156 g of soft monomer butyl acrylate, 36 g of hard monomer benzyl acrylate, 6 g of cross-linking monomer hydroxyethyl acrylate, and 2 g of cross-linking monomer acrylic acid were put into a 1L four-necked flask, heated to 78°C, and then 0.16 g of BPO was added to react for 10 hours, during which time the mixture was diluted with solvent. After the reaction was completed, the mixture was cooled and diluted to a solid content of 20%, to obtain an acrylate copolymer; the acrylate copolymer had a weight average molecular weight of 147 W and a PDI of 8.2; Mix 100 parts of the above-mentioned acrylic ester copolymer, 0.2 parts of toluene diisocyanate, 0.02 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, and 0.2 parts of antistatic agent, and mechanically stir for 10-15 minutes; The uniformly stirred mixture was coated on a 50 μm thick release film, baked in an oven at 120° C. for 3 min, attached to a polarizer, and aged at 35° C. for 5 days to obtain an acrylate copolymer pressure-sensitive adhesive.
2. A method for preparing an acrylic copolymer pressure-sensitive adhesive, characterized in that: The following steps are involved: 300 g of solvent ethyl acetate, 156 g of soft monomer butyl acrylate, 36 g of benzyl acrylate, 4 g of cross-linking monomer hydroxyethyl acrylate, and 4 g of cross-linking monomer acrylic acid were put into a 1L four-necked flask, heated to 78°C, and then 0.16 g of BPO was added to react for 10 hours, during which time the mixture was diluted with solvent. After the reaction was completed, the mixture was cooled and diluted to a solid content of 20%, to obtain an acrylate copolymer; the acrylate copolymer had a weight average molecular weight of 137 W and a PDI of 7.4; Mix 100 parts of acrylate copolymer, 0.2 parts of toluene diisocyanate, 0.02 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, and 0.2 parts of antistatic agent, and stir mechanically for 10-15 minutes; The uniformly stirred mixture was coated on a 50 μm thick release film, baked in an oven at 120° C. for 3 min, and bonded to a polarizer to obtain an acrylate copolymer pressure-sensitive adhesive.
3. The method for preparing the acrylic ester copolymer pressure-sensitive adhesive according to claim 1 or 2, characterized in that: The thickness of the adhesive film formed after coating on the release film is 5-30 μm.
Citation Information
Patent Citations
Optically compensated acrylic pressure-sensitive adhesive composition, polarizing plate and liquid crystal display device containing the same
CN101495586A
Acrylic adhesive composition, adhesive obtained using same, polarizing plate adhesive, and image display device
CN109476971A
Pressure-sensitive-adhesive polarizing film, and laminate for image display device
TW202219561A